2017
DOI: 10.3389/fnsys.2017.00024
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Frontal Alpha-Band Power Correlates with Preoperative Neurocognitive Function in Older Adults

Abstract: Each year over 16 million older Americans undergo general anesthesia for surgery, and up to 40% develop postoperative delirium and/or cognitive dysfunction (POCD). Delirium and POCD are each associated with decreased quality of life, early retirement, increased 1-year mortality, and long-term cognitive decline. Multiple investigators have thus suggested that anesthesia and surgery place severe stress on the aging brain, and that patients with less ability to withstand this stress will be at increased risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 72 publications
7
112
0
2
Order By: Relevance
“…43,41 Further, in a patient population >60 yr old, intraoperative alpha power negatively correlated with cognitive performance before operation. 44 Our study supports a possible link between alpha power and the 'cognitive state' of the brain. A published case report describes a patient who repeatedly developed PACU-D and did not have any alpha spindle containing trajectory during emergence, and had alpha-spindle characteristics that resembled a much older patient.…”
Section: Discussionsupporting
confidence: 77%
“…43,41 Further, in a patient population >60 yr old, intraoperative alpha power negatively correlated with cognitive performance before operation. 44 Our study supports a possible link between alpha power and the 'cognitive state' of the brain. A published case report describes a patient who repeatedly developed PACU-D and did not have any alpha spindle containing trajectory during emergence, and had alpha-spindle characteristics that resembled a much older patient.…”
Section: Discussionsupporting
confidence: 77%
“…The sample size of 53 patients (maximum of 50 for any given data epoch, table 1) is consistent with (and exceeds) previous efforts investigating whole-scalp oscillatory electroencephalographic patterns in adult surgical patients. 5,26,27 For static connectivity analysis, statistical comparisons were performed using linear mixed models (IBM SPSS Statistics version 24.0 for Windows; IBM Corp. USA) to test (1) the difference between the nine studied epochs for both frontal-parietal and prefrontal-frontal connectivity measures, and (2) the difference between frontal-parietal and prefrontal-frontal connectivity. Linear mixed modeling analysis offers more flexibility with missing values and accounts for individual differences by including a random intercept associated with each participant.…”
Section: Discussionmentioning
confidence: 99%
“…Giattino et al recently demonstrated that intraoperative frontal alpha oscillation power was positively correlated with neurocognitive function (Giattino et al , 2017). In other compelling studies, a thiopental challenge resulted in decreased frontal beta oscillation power in Alzheimer’s disease patients (Holschneider et al , 1997, Holschneider et al , 2000).…”
Section: Discussionmentioning
confidence: 99%